2020
DOI: 10.1049/iet-nbt.2019.0188
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of eco‐friendly and recyclable Pd/LDHs catalyst using the withered leaves extract for Suzuki coupling reaction

Abstract: The hydrotalcite-supported palladium (Pd) catalyst is prepared with a green and environmentally friendly route, introducing the extract of withered leaves as a dispersant and reducing agent (Pd/LDHs-B). Compared with the as-prepared catalyst (Pd/LDHs-P with the average diameter of 4.3 nm) using a chemical synthesis method with polyvinylpyrrolidone as a dispersant and ascorbic acid (Vc) as a reductant, the results indicate that the size of Pd nanoparticles in Pd/LDHs-B is smaller (ca. 3.6 nm). The Pd-LHDs-B (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Nowadays, scientists have concentrated on the expansion of nanotechnology‐based drug delivery systems, which offer promising prospects for delivering the desired quantity of the drugs into target sites, in addition to cell penetration efficiency. In this respect, metallic nanoparticles (NPs) have received a great deal of interest among researchers as they offer a number of attractive characteristics, such as lower toxicity, high surface‐to‐volume ratio and super‐durability [6, 7]. Recent developments have demonstrated that zinc oxide NPs (ZnONPs) are promising candidates due to their potential to produce reactive oxygen species (ROSs), which show a major role in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, scientists have concentrated on the expansion of nanotechnology‐based drug delivery systems, which offer promising prospects for delivering the desired quantity of the drugs into target sites, in addition to cell penetration efficiency. In this respect, metallic nanoparticles (NPs) have received a great deal of interest among researchers as they offer a number of attractive characteristics, such as lower toxicity, high surface‐to‐volume ratio and super‐durability [6, 7]. Recent developments have demonstrated that zinc oxide NPs (ZnONPs) are promising candidates due to their potential to produce reactive oxygen species (ROSs), which show a major role in biological systems.…”
Section: Introductionmentioning
confidence: 99%